2017
DOI: 10.3390/ijms18071411
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolus: In Genome Maintenance and Repair

Abstract: Abstract:The nucleolus is the subnuclear membrane-less organelle where rRNA is transcribed and processed and ribosomal assembly occurs. During the last 20 years, however, the nucleolus has emerged as a multifunctional organelle, regulating processes that go well beyond its traditional role. Moreover, the unique organization of rDNA in tandem arrays and its unusually high transcription rates make it prone to unscheduled DNA recombination events and frequent RNA:DNA hybrids leading to DNA double strand breaks (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 158 publications
(182 reference statements)
3
72
0
1
Order By: Relevance
“…Accordingly, upon PLK4 inhibition, we detected the formation of RNA:DNA hybrids by immunostaining with the monoclonal antibody S9.6 directed against these structures (Figure 6 A, B). Upon staining fixed cells in situ, the immunofluorescence signal derived from antibody binding was prominent in discrete nuclear structures, compatible with the concept that R-loops mainly occur at specific sites of highly active transcription (Tsekrekou et al, 2017). In contrast, the overexpression of RNaseH1, an RNase that specifically cleaves the RNA component of RNA:DNA hybrids, strongly reduced the nuclear immunostaining signal, confirming the specificity of the antibody (Figure 6 A To clarify the causal link between R-loop formation and replication stress, we performed fiber assays.…”
Section: Centrosome Disintegration Induces Rna:dna Hybrids and This supporting
confidence: 76%
“…Accordingly, upon PLK4 inhibition, we detected the formation of RNA:DNA hybrids by immunostaining with the monoclonal antibody S9.6 directed against these structures (Figure 6 A, B). Upon staining fixed cells in situ, the immunofluorescence signal derived from antibody binding was prominent in discrete nuclear structures, compatible with the concept that R-loops mainly occur at specific sites of highly active transcription (Tsekrekou et al, 2017). In contrast, the overexpression of RNaseH1, an RNase that specifically cleaves the RNA component of RNA:DNA hybrids, strongly reduced the nuclear immunostaining signal, confirming the specificity of the antibody (Figure 6 A To clarify the causal link between R-loop formation and replication stress, we performed fiber assays.…”
Section: Centrosome Disintegration Induces Rna:dna Hybrids and This supporting
confidence: 76%
“…Although separated by the nuclear envelope, nuclear and cytoplasmic RNA granules can share protein components and may communicate [14]. As nuclear bodies have been discussed in detail [12, 15, 16], we focus here on somatic RNA granules in the cytoplasm and their roles in cellular and tissue maintenance.…”
Section: Rna Granules: Location Composition and Size Mattermentioning
confidence: 99%
“…Nucleoli are the most prominent RNA granules in the nucleus; they assemble ribosomes, assist in genome maintenance and facilitate DNA repair. Moreover, nucleoli control stress responses, cell senescence, and apoptosis [12]. Thus, they are indispensable for the maintenance of nucleated somatic cells.…”
Section: Rna Granules: Location Composition and Size Mattermentioning
confidence: 99%
“…In this study, we paid attention to human ribosomal DNA (rDNA) repeat unit, which repeats hundreds of times in diploid human genome. Human rDNA clusters on the short arms of the five acrocentric chromosomes (chromosomes 13,14,15,21,22), and contains a 13-kb transcribed region and a 30-kb intergenic spacer (IGS). Transcribed region encodes 18S, 5.8S and 28S ribosomal RNA.…”
mentioning
confidence: 99%
“…Recently, a study identified 49 conserved regions in IGS through comparative genome in multiple species [14] and revealed the regulation potentials of IGS. rDNA is the fundamental genomic element to form nucleolus where ribosomes assemble together [15,16] and its transcriptional RNA product -ribosomal RNA is indispensable parts of ribosome, which suggests rDNA stability is vital for normal biology processes. Copy number variation of rDNA balances rDNA dosage [17]and is associated with the expression of several functional coherent gene sets [18].…”
mentioning
confidence: 99%